Answers

  • Brainly User
2016-01-06T01:58:14+08:00
F(x) = 3x + 15 
y = 3x + 15

A.  To solve for y-intercept, substitute 0 for x:
   y = 3x  15
   y = 3 (0) + 15
   y = 15
   y-intercept is at  (0,15)

B.  To solve for x-intercept, substitute 0 for y:
   y = 3x + 15
   0 = 3x + 15
   3x = -15
   3x/3 = -15/3
   x = -5
   x-intercept is at (-5,0)
0
2016-01-06T20:33:03+08:00
Y = mx + b  
f(x) = 3x + 15
y = 3x +15

y-intercept is simply the value of y when x is zero. Also b in the equation so 15.
x-intercept is the value of x when y is zero.
y = 3x + 15
0 = 3x + 15
-3x = 15
-3x/-3 = 15/-3
x = -5 
0